Excellence by Simplicity: Life and Contributions of Professor Ramesh Maheshwari (1940-2019) - Keyur Adhvaryu (Fungal Genetics Reports, 2019)
Professor Ramesh Maheshwari passed in Bangalore on 30 March 2019. His work generated fundamental understanding in diverse areas of fungal biology including the germination and infection of plants by rust fungi, the life-cycle of Neurospora in its natural habitat; fungal senescence and heterokaryosis, and the production of microconidia in fungi. He was a member of many professional societies including the American Society of Plant Physiologists, Society of Microbiologists of India, and the Indian Phytopathological Society, and he served on the Editorial Board for Journal of Genetics. He nurtured scientific curiosity in his students and colleagues.